2009
DOI: 10.1177/0731684409102836
|View full text |Cite
|
Sign up to set email alerts
|

SIF for Double- and Single-sided Composite Repair in Mode I and Mixed Mode

Abstract: In this study, the finite element is used to analyze and compare the performances of the double-and single-sided composite repair in aircraft structures in mode I and mixed mode. The stress intensity factors in modes I and II at the crack tip are computed to perform the objective of the study. The effects of the different parameters of repair such as adhesive and patch properties on the SIF variation were highlighted. The obtained results show that the adhesive properties must be optimized in order to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Putting Equation (12) into Equation (2) gives the differential equation of interfacial temperature strain distribution:…”
Section: Analytical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Putting Equation (12) into Equation (2) gives the differential equation of interfacial temperature strain distribution:…”
Section: Analytical Modelmentioning
confidence: 99%
“…Although extensive experimental, analytical and numerical studies on the delamination of composite sandwich materials have been conducted in recent years [5][6][7][8][9][10][11][12][13][14][15], most of them ignored the effects of environmental temperature on the interfacial delamination behaviour. It is well known that composite skins and core materials are sensitive to temperature, the mechanical performance and interfacial behaviour change with the environmental temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of experimental and analytical researches on the delamination of composite sandwich materials have already been carried out in the past decades. 26 Vadakke and Carlsson 7 investigated the interfacial bonding properties between the surface layer and the foam core material. The test results showed that the interfacial bonding strength was significantly affected by the density of foam core.…”
Section: Introductionmentioning
confidence: 99%
“…The authors 21,22 have highlighted the advantage of the double-sided patch repair compared to single-sided patch repair on the reduction of the SIF. They indicated that the adhesive properties must be optimized in order to increase the advantage of the double-sided patch and to avoid adhesive failure.…”
Section: Introductionmentioning
confidence: 99%